A bilingual news webpage ideology translation - Salis Radiaty Mu'amanah; Unpris Yastanti (LADU: Journal of Languages and Education, 2021)
Background: Cultural problem commonly arising in translation is related to the cultural differences between the two languages involved. However, deciding what ideology should be used in the translation process is complicated. Purpose: This paper aims to give the explanation to the readers about the type and dominant ideology of translation in the article of www.Berita2Bahasa.com. Design and methods: To answer the purpose, this study uses the descriptive method to analyze those articles. The data were gathered based on news from May 29 – June 3, 2017. To analyze the data, first step is deciding the right topic, writer chooses the article. The writer also prepares the theories to support the analysis Results: This study revealed that in each article of www.Berita2Bahasa.com, the translator uses 2 type ideology of translation, those are Domestication and Foreignization Ideology. Most of articles is dominantly used domestication Ideology.